Direct nanometer-scale patterning by the cantilever oscillation of an atomic force microscope - Hyon, CK; Choi, SC; Hwang, SW; Ahn, D; Kim, Y; Kim, EK (AMER INST PHYSICS, 1999)
A resistless nanostructure patterning technique using tip oscillation of an atomic force microscope (AFM) was systematically investigated. Commercial AFM cantilevers are used to successfully generate patterns as narrow as 10 nm on a GaAs surface, without further sharpening of the tips. Reliable patterns with fully controlled width and depth are achieved by adjusting the feedback gain and the scan speed. This process allows nanometer-scale patterning to be performed simply, and is well suited for nanodevice fabrication. (C) 1999 American Institute of Physics. [S0003-6951(99)03828-0].
Keywords: SCANNING TUNNELING MICROSCOPE; LITHOGRAPHY; TRANSISTOR